Mercury in soils and phytocenoses of the Kiev region, accumulation mechanism and distribution forms - Ковальчук, В. (Київський національний університет імені Тараса Шевченка, 2011)
A general mechanism of distribution of mercury in soils is being shown. This article characterizes the content and distribution of the mercury in Kiev region soils. The effect of different doses of mercury on the plant growth is being studied based on the example of the barley growth.

Розглянуто загальний механізм поширення ртуті в ґрунтах. Охарактеризовано вміст та поширення ртуті в ґрунтах Київщини. Досліджено вплив різних доз ртуті на розвиток рослин на прикладі ячменю.
Ртуть в ґрунтах та фітоценозах Київщини, механізм накопичення та форми поширення
Keywords: mercury; soil; phytocenoses; Kiev region; heavy metals; ртуть; ґрунти; фітоценози; Київщина; важкі метали